Outcomes and effectiveness of antiretroviral therapy for HIV-infected children in South African treatment cohorts - Davies, Mary-Ann (Department of Public Health and Family Medicine, 2024)
Since 2004, increasing numbers of children in sub-Saharan Africa have commenced antiretroviral therapy (ART). This thesis reviews the outcomes of published studies of paediatric ART cohorts in Africa, describes outcomes for children receiving ART in South Africa and examines determinants of mortality and generalizability across the Southern African region. Temporal trends in characteristics at ART initiation are also examined. The measurement of treatment success in resource-limited settings is reviewed, by examining virological failure, and assessing the diagnostic accuracy of immunological criteria for identifying virological failure.The results chapter is presented in the form of published or submitted papers based on data from the International epidemiologic Databases to Evaluate AIDS-Southern Africa (IeDEASA) collaboration. The first paper reviews paediatric ART studies from Africa published before 2008. Together with the literature review in chapter 1, it provides the background to this thesis. The second paper reports on mortality (8%) and retention in care (81%) by 3 years after ART start for > 6,000 children who initiated ART in South Africa. The generalizable prognostic models in the third paper suggest that mortality during the first year on ART ranges from <2% to >45%, with the majority of children being in the group with the best prognosis. The fourth paper reports that 1 in 5 children meet criteria for confirmed virological failure by 3 years on ART. The risk is greater with triple ART containing nevirapine or unboosted ritonavir (in comparison with lopinavir/ritonavir or efavirenz). The fifth and sixth papers demonstrate that immunological criteria have low sensitivity and positive predictive value for virological failure. Targeted viral load measurement reduces the number of false positive virological failure diagnoses. The final paper shows that increasing numbers of children have initiated ART with a decline in disease severity at therapy start from 2005-2010. However, even in 2010 a substantial number of children started ART with advanced disease. The thesis concludes that access to ART for children has increased, with good outcomes. HIV cohort research is important in evaluating the safety and effectiveness of different models of care, treatment and monitoring strategies.